ISOLASI CAPSAICIN DARI OLEORESIN CABAI RAWIT - Thaib, Novita; Katja, Dewa Gede; Aritonang, Henry Fonda (CHEMISTRY PROGRESS, 2015)
This study aims to isolate the capsaicin of cayenne pepper oleoresin by extraction method. The results obtained as much as 0.5 g (0.5%) products of 100 g of dried cayenne pepper. Product is colorless crystalline solid (clear), a melting point of 66 oC and a refractive index of 1.4694. Crystals were analyzed with an infrared spectrophotometer (IR), namely the OH group (3409.9 cm-1 and 1026.1 cm-1), NH stretching and bending (3278.8 cm-1, 1515.9 cm-1 and 920 cm-1) which is a secondary amide, C=C (1643.2 cm-1), CH stretching from CH3 and CH2 (2927.7 cm-1 and 2854.5 cm-1) and CH bending of CH2 and CH3 (1461.9 cm-1 and 1377.1 cm-1), C=O (1747.4 cm-1) and group O-CH3 asymmetric and symmetric (1253.6 cm-1 and 1164.9 cm-1).Penelitian ini bertujuan untuk mengisolasi capsaicin dari oleoresin cabai rawit metode refluks menggunakan pelarut kloroform. Hasil yang diperoleh sebanyak 0,5 g (0,5 %) produk dari 100 g cabai rawit kering. Produk berupa padatan kristal tak berwarna (bening), titik leleh 66 dan indeks bias 1,4694. Kristal yang diperoleh dianalisis dengan spektrofotometer infra merah (IR), yaitu adanya gugus OH (3409,9 cm-1 dan 1026,1 cm-1), NH stretching dan bending (3278,8 cm-1, 1515,9 cm-1 dan 920 cm-1) yang merupakan suatu amida sekunder, C=C (1643,2 cm-1), CH stretching dari CH3 dan CH2 (2927,7 cm-1 dan 2854,5 cm-1) dan CH bending dari CH2 dan CH3 (1461,9 cm-1 dan 1377,1 cm-1), C=O (1747,4 cm-1) serta gugus O-CH3 asimetrik dan simetrik (1253,6 cm-1 dan 1164,9 cm-1).